Eccentric cycling rehabilitation after anterior cruciate ligament reconstruction: a randomised controlled trial of strength and biomechanical outcomes - Milandri, Giovanni (Department of Human Biology, 2017)
After anterior cruciate ligament reconstruction (ACL-R), persistent strength and biomechanical deviations remain. Reducing these by training may reduce risk of re-injury or osteoarthritis for these patients. A cross-sectional study investigated biomechanics of ACL-R male patients long-term (~5 years) post surgery. Fifteen ACL-R and fifteen healthy controls were tested in walking and running using motion capture. Devi- ations were found, primarily between-limbs, and also between groups. Largest deviations were lower knee angles and moments in the affected limb during running. However, these were not found during walking; thus, differences were highlighted by the higher-intensity task. During running, knee abduction moment was lower (more valgus) for the affected compared to unaffected and control limbs. The larger effects in moment show greater clinical potential than knee valgus angle. The ACL-R patients had lower impact foot strike during running than controls. The above results indicate chronic, clinical changes in joint loading. A randomised controlled intervention trial evaluated progressive eccentric cycling for ACL-R males, compared to concentric controls. This is one of the first trials of eccentric vs. concentric training for ACL-R, matched by rating of perceived exertion. Twenty-six adult males, 12 weeks post hamstring-graft ACL-R trained three times/week for 8 weeks under supervision. During training the eccentric group limb powers absorbed were higher than those produced by the concentric group, with a lower heart rate. For both groups, pain scores were low, and one of the patient-reported outcomes (IKDC) improved. Hamstring strength increased in the eccentric group by 15%, but this was not seen in the concentric group. For both groups, 60°/s quadriceps strength increased by a similar amount, approximately 28%. Biomechanically, eccentric training was more effective than matched concen- tric training at resolving knee (P=0.022, walk) and hip (P =0.010, run) flexion angle deviations in the affected limb. In both groups, knee extension moments increased, reducing asymmetries. Large knee abduction moment deviations at baseline were not reduced by either programme (P >0.05). At follow-up (~6 months), both groups showed similar return-to-sports progress; several patients passed using one criterion (IKDC), and none passed using a stricter four-criteria method (Univ. Delaware). Thus it can be concluded that for adult ACL-R males, eccentric cycle training is clinically acceptable, with similar or in some cases better outcomes than concentric cycle training. It improves patient-reported outcomes, strength recovery, biomechanical deviations, and return-to-sports measures.